Techniques for Effective Optical Noise Rejection in Amplitude-Modulated Laser Optical Radars for Underwater Three-Dimensional Imaging. (8th February 2010) - Ricci Ricci, R. R.; Francucci Francucci, M. M.; De Dominicis De Dominicis, L. L.; Ferri de Collibus Ferri de Collibus, M. M.; Fornetti Fornetti, G. G.; Guarneri Guarneri, M. M.; Nuvoli Nuvoli, M. M.; Paglia Paglia, E. E.; Bartolini Bartolini, L. L.
Abstract : Amplitude-modulated (AM) laser imaging is a promising technology for the production of accurate three-dimensional (3D) images of submerged scenes. The main challenge is that radiation scattered off water gives rise to a disturbing signal (optical noise) that degrades more and more the quality of 3D images for increasing turbidity. In this paper, we summarize a series of theoretical findings, that provide valuable hints for the development of experimental methods enabling a partial rejection of optical noise in underwater imaging systems. In order to assess the effectiveness of these methods, which range from modulation/demodulation to polarimetry, we carried out a series of experiments by using the laboratory prototype of an AM 3D imager (λ = 405 nm) for marine archaeology surveys, in course of realization at the ENEA Artificial Vision Laboratory (Frascati, Rome). The obtained results confirm the validity of the proposed methods for optical noise rejection.